Internationalization project of tulea globulus - an in-depth market analysis of France - Paes, Frederico Allen de Vasconcelos (2023)
This thesis guides Globulus, a Portuguese forestry company within the Tulea group, in its international expansion. Globulus currently cultivates and sells Eucalyptus globulus for the pulp and paper industry in Portugal. International market selection through country ranking, clustering, and analysis of the five most promising markets, revealed Spain as the most attractive market for internationalization. This is supported by industry indicators, financial viability, and Globulus’ preferences. The proposed entry mode is indirect exporting, backed by a detailed marketing plan and financial projections. Recommendations include monitoring wood prices and transport costs, establishing an international partner network, and diversifying the product portfolio.